J. M. van Ophuijsen, Hephaestion on Metre. A Translation and Commentary, Supplements to Mnemosyne 100, Leiden-New York-Kobenhavn-Köln, Brill, 1987, 186 pp. ISBN 90-04-08452-5 (Minerva, 2019)
Review: J. M. van Ophuijsen, Hephaestion on Metre. A Translation and Commentary, Supplements to Mnemosyne 100, Leiden-New York-Kobenhavn-Köln, Brill, 1987, 186 pp. ISBN 90-04-08452-5